2021
DOI: 10.1108/jeim-11-2020-0445
|View full text |Cite
|
Sign up to set email alerts
|

Consequential factors of Big Data's Analytics Capability: how firms use data in the competitive scenario

Abstract: PurposeThe article's objective is to analyze the consequent factors of Big Data Analytics Capability for firms in the competitive scenario, using different analytical models.Design/methodology/approachThe research had a quantitative approach, using a survey of data from firms located in the state of São Paulo – Brazil. Structural Equation Modeling (SEM) was used to validate the model.FindingsThe results reveal that all hypotheses were accepted. Business value was the construct that had the most explanatory pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The advent of “Big Data” has transformed the firms' working styles (Peng et al. , 2022; Contreras Pinochet et al., 2021) and enforces a firm's top management to bring changes in their production system to capture a competitive advantage in the highly globalized markets (Aydiner et al ., 2019). Yang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of “Big Data” has transformed the firms' working styles (Peng et al. , 2022; Contreras Pinochet et al., 2021) and enforces a firm's top management to bring changes in their production system to capture a competitive advantage in the highly globalized markets (Aydiner et al ., 2019). Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hadoop and MapReduce), which are used to create valuable insights from the large amount of dataset, are referred as big data use (BDU) (Sun and Shi, 2021;Chen et al, 2012). The advent of "Big Data" has transformed the firms' working styles (Peng et al, 2022;Contreras Pinochet et al, 2021) and enforces a firm's top management to bring changes in their production system to capture a competitive advantage in the highly globalized markets (Aydiner et al, 2019). Yang et al (2022) highlighted that big challenges using big data can be resolved to minimize the financial risk in the digital economy.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Zhan et al (2017), who develop a conceptual framework by analyzing the literature and interviews with managers and academics, it is suggested that BDAC, in addition to accelerating the innovation processas it helps to quickly detect product weaknesses and functionalities valued by customersalso facilitates the identification and prioritization of customer needs in specific markets. Contreras Pinochet et al, (2021) concluded that BDAC enables the business to analyze customer data in real time and produce insightful information that is useful for creating solutions to maintain or enhance market position.…”
Section: Big Data Analytics Capability and Innovation Capabilitymentioning
confidence: 99%
“…The article entitled "Consequential factors of Big Data's Analytics Capability: how firms use data in the competitive scenario" is contributed by Contreras Pinochet et al (2021). Their focus on big data analytics capability leads to a proposed model that encompasses big data operations, updating IT to enable big data, advanced big data analytics skillsets, and the strategic use of big data.…”
Section: Consequential Factors Of Big Data's Analytics Capability: How Firms Use Data In the Competitive Scenariomentioning
confidence: 99%